Comparison of Soluble fms-Like Tyrosine Kinase-1 (SFLT-1) between Normal and Severe Pre-eclampsia in Pregnant Women, Medan, Indonesia - Lamtiar, Rebecca Rumesty; Mutiara, Erna; Raja, Sarma N Lumban (Indonesian Journal of Medicine, 2016)
Background: The pathogenesis of pre-eclampsia as a primary cause of mortality among pregnant women remains unclear. It was suggested that angiogenic factors such as Soluble fms-Like Tyrosine Kinase-1 (SFLT-1) play an important role in the causal mechanism of pre-eclampsia/ eclampsia. This study aimed to compare the SFLT-1 level in pre-eclampsia/eclampsia in pregnant women with that in normotensive pregnant women.Subjects and Method: This was an analytic observational conducted at three hospitals: Haji Adam Malik, Pirngadi, and Sundari Hospitals, Medan, Indonesia, from September to December 2014. A total sample of 60 pregnant women of the third trimester, including those with severe pre-eclampsia/eclampsia and normotensive women, was selected for this study. The level of serum SFLT-1 was measured by ELISA method. The difference in mean of serum SFLT-1 levels between the two groups was tested by Mann-Whitney.Results: The mean of serum SFLT-1 level in women with preeclampsia was higher (mean=1692.69pg/ml; SD=540.64) than that in normotensive women (mean=1348.52pg/ml; SD=649.83). This difference was statistically significant (p=0.040).Conclusion: Level of serum SFLT-1 in women with severe pre-eclampsia/eclampsia is significantly higher than that of normotensive women.Keywords: serum SFLT-1, pre-eclampsia, pregnant womenCorrespondence:ÃÂ Rebecca Rumesty Lamtiar. Department of Physiology, Faculty of Medicine, HKBP Nommensen University, Medan.Indonesian Journal of Medicine (2016), 1(2): 84-89https://doi.org/10.26911/theijmed.2016.01.02.01